Pengaruh Kualitas Manajemen Kas terhadap Peningkatan Kinerja Bisnis Perusahaan: - Acep Samsudin; Lia Nirawati; Miranda Maharani; Riva Dika Adhilni; Firdha Amalia Nareswari; Halid Adli (Transformasi Manageria: Journal of Islamic Education Management, 2023)
Cash management is the optimization of cash flow and excess cash investment. Financial statements are a form of management accountability in managing the company's resources as well as information that reflects the company's performance. This study aims to determine the effect of cash management quality on improving a business performance on CV. Alphie in the period 2019-2021. The method used in this study is a quantitative method. The results showed that cash and company performance stimulant positive and significant effect on residual, but partial cash does not have a positive and significant effect on residual. Keywords: Cash Management, Company, Residual.